(untitled) (UTC Prospectivas: Journal of Administrative and Economic Sciences, 2025)
The Ecuadorian financial market has historically favored the indirect intermediation of resources through financial institutions. However, the stock market, which favors the direct channeling of resources, offers bonds, a financing instrument that can be considered an alternative to bank credit. The objective of this paper is to analyze the competitiveness of bond issuance as a financing option compared to bank credit. For this purpose, information from the Central Bank of Ecuador and the Quito Stock Exchange was used, the method of successive approximations was employed, and the weighted averages of interest rates in two periods of bank loans in the corporate productive segment were compared with the yields paid by companies that financed themselves in the stock market through bond issues. After contrasting the hypotheses, it is determined that in the first period (2002-2007) bonds cost less than bank credit; while, in the second period (2017-2021) bonds cost more than bank credit. These results revealed, for the corporate productive segment, that financing through bonds went from being a less expensive alternative in the initial period, to having a higher cost than bank credit in the second period of the study.